Natural Interaction Design for Navigation in Virtual Environment of Sino-Portuguese Architecture in Museum - KALARAT, Kosin; RATTANARUNGROT, Sasithorn (Walailak Journal of Science and Technology (WJST), 2020)
Virtual Environment (VE) is an artificial environment created for providing the information in Virtual Reality (VR). The audiences are able to obtain the information via interaction to the environment. Virtual Reality for Culture heritage buildings, which are inherited from past generations and maintained in the present, is an interested topic because its contents often built for giving the information and knowledge about the past to the new generation in virtual museums. However, there is a limitation of Virtual Reality (VR) applications in reproducing cultural sites as most of these applications are not successful in catching public’s attention and involvement. In this research, we focus on using Natural Interaction (NI) interfaces based on a body movement in Virtual Reality for museums to grab attention from audience and to increase public’s involvement. This paper presents the development of Natural Interaction using Microsoft Kinect to define the new grammar of gesture for Sino Portuguese Architecture which is a cultural heritage of Thailand. Results of early tests improved the prototype in progress which alllows more complexity in natural interchanges and connection between users and virtual world. The final result was evaluated after the system was installed in Peranakannitat museum and by interviewing 6 docents. It was found that our system was easy to use as it took only about 3 - 5 min to familiarize the system for navigation in the virtual environment without recognizing the grammar of gesture commands.